Laparoscopy treatment of liver abscess secondary to an unusual foreign body (rosemary twig) - André Thá Nassif; Victor Hugo Granella; Tulio Rucinski; Bruno Landal Cavassin; Alesandra Bassani; Lucas Thá Nassif (University of São Paulo, 2021)
A hepatic abscess caused by a swallowed foreign body is a rare and challenging diagnosis. Most patients have nonspecific symptoms, and more than 90% of patients do not remember having swallowed it, which occurred accidentally. In this setting, fish bones, chicken bones, and toothpicks are the most found foreign bodies. We reported the case of a 54-year-old male patient admitted with abdominal pain and intermittent fever. He was diagnosed with liver abscess and treated successfully with antibiotics and a laparoscopic procedure; a rosemary twig was found during the abscess drainage procedure. Furthermore, a literature review of 22 cases of laparoscopic treated liver abscesses associated with a foreign body was made.